PERAN TAMAN BACA MASYARAKAT SILAYUNG DALAM MENINGKATKAN LITERASI INFORMASI - Fatur Prahardika (IKIP Siliwangi, 2020)
ABSTRACT The ability of the community and knowledge become more developed after the presence of communication and information technology. Information literacy can also be termed as ‘information literacy, even in various scientific meetings / forums it is often discussed about this information literacy. Information literacy can also be interpreted as a series of skills for finding, receiving, processing, and utilizing information to others to complete and find a solution, therefore information literacy is needed because of the rapid advances in technology today. Diverse information among the people today causes people to need expertise, one of which is expertise about information. The amount of information available makes the searchers and users of information confused to get relevant information. A method is needed to find information from various sources of information that are developing. Literacy can help to find the information needed quickly, easily and relevant. This study uses a qualitative descriptive approach, meaning that the data collected is not in the form of numbers, but the data comes from interview scripts, field notes, personal documents, memo notes, and other official documents. The purpose of this study is to determine the Silayung TBM management process in improving information literacy.ABSTRAKKemampuan masyarakat serta pengetahuan menjadi semakin berkembang setelah kehadirannya teknologi komunikasi dan informasi. Literasi informasi dapat di istilahkan juga dengan istilah ‘melek informasi, bahkan diberbagai pertemuan/forum ilmiah juga sering didiskusikan mengenai literasi informasi ini. Literasi informasi juga dapat diartikan sebagai serangkaian keterampilan untuk mencari, menerima, mengolah, dan memanfaatkan informasi kepada orang lain untuk menyelesaikan dan mencari jalan keluarnya, maka dari itu literasi informasi sangat dibutuhkan karena pesatnya kemajuan teknologi saat ini. Informasi yang beragam dikalangan masyarakat saat ini menyebabkanmasyarakat memerlukan keahlian, salah satunya keahlian yaitu tentang informasi. Banyaknya informasi yang tersedia membuat pencari dan pengguna informasi kebingungan untuk mendapatkan informasi yang relevan. Diperlukan sebuah metode untuk mencari informasi dari berbagai sumber informasi yang berkembang. Literasi dapat membantu untuk menemukan informasi yang dibutuhkan secara cepat, mudah dan relevan.Penelitian ini menggunakan pendekatan deskriptif kualitatif, artinya data yang dikumpulkan bukan berupa angka-angka, melainkan data tersebut berasal dari naskah wawancara, catatan lapangan, dokumen pribadi, catatan memo, dan dokumen resmi lainnya. Tujuan penelitian ini yaitu untuk mengetahui proses pengelolaan TBM Silayung dalam meningkatkan Literasi informasi.ABSTRACT The ability of the community and knowledge become more developed after the presence of communication and information technology. Information literacy can also be termed as ‘information literacy, even in various scientific meetings / forums it is often discussed about this information literacy. Information literacy can also be interpreted as a series of skills for finding, receiving, processing, and utilizing information to others to complete and find a solution, therefore information literacy is needed because of the rapid advances in technology today. Diverse information among the people today causes people to need expertise, one of which is expertise about information. The amount of information available makes the searchers and users of information confused to get relevant information. A method is needed to find information from various sources of information that are developing. Literacy can help to find the information needed quickly, easily and relevant. This study uses a qualitative descriptive approach, meaning that the data collected is not in the form of numbers, but the data comes from interview scripts, field notes, personal documents, memo notes, and other official documents. The purpose of this study is to determine the Silayung TBM management process in improving information literacy.